Beginning HTML5 & CSS3 for dummies - Tittel, Ed; Minnick, Chris (--For dummies., 2013)
Your full-color, friendly guide to getting started with HTML5 and CSS3! HTML and CSS are essential tools for creating dynamic websites and help make your websites even more effective and unique. This friendly-but-straightforward guide gets you started with the basics of the latest versions of HTML and CSS: HTML5 and CSS3. Introducing you to the syntax and structure of the languages, this helpful guide shows you how to create and view a web page, explains ideal usage of HTML5 and CSS3, walks you through the CSS3 rules and style sheets, addresses common mistakes and explains how to f.